Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2020)
This issue of KIU Journal of Humanities touches on Development Administration, Religious Studies, Literary Studies, Peace and Conflict Studies, Social Psychology and Educational Psychology. The first part of the Journal addresses issues in Development Administration such as rightsizing, restructuring, public service ethics, tax administration, anti corruption programmes and so on. It is revealed in one of the papers that that the print media was instrumental to anti-corruption programmes during the period of the study (1999-2019). The paper recommended that the print media should engage more in investigative journalism, develop the political-will to fight corruption, and proprietors should desist from unduly influencing journalists while performing official duties to enable the print media contribute better towards the implementation of anti-corruption programmes in Nigeria. In part two, the importance of Religious Studies is emphasized. One of the papers focuses on the extent to which contemporary Yoruba Muslims comply with regulations on the practice of widowhood in the face of cultural interference. This is because, according to the paper, Islam also has a comprehensive rule regulating the practice of widowhood for Muslims in such a way Muslim women are guaranteed right to cleanliness, freedom and decency during this period. In Section Three, literary works of Ngugi wa Thiong’o, Niyi Osundare, Kourouma and Mikhail Bulgakov are x-rayed. One of the papers centres on the socio-economic realities and leadership styles of African rulers, which portrays the disregard of fellow Africans. It reveals the disappointment and agony of the teeming mass of the continent in the post-colonial and modern periods. Section Four looks into the problem of insurgency in North Eastern Nigeria with a view to profering solutions to it. One of the papers in this section argues that Boko Haram Insurgency has a negative impact on human security, and recommends that counterinsurgency can only be successful when poverty, corruption and bad governance problems are handled effectively. Section Five examines certain social factors which influence students’ learning skills. Some of these include social economic background, environmental and health needs. It is disclosed in one of the papers that all the social factors are potent in differentiating adolescents’ level of psychological well-being. It is concluded that the home environment should be a strong source of support for developing adolescents’ psychological wellbeing by providing close relationships, strong parenting skills, good communication, and modeling positive behaviour. Therefore, modifications in the home environment should be made more favourable for the enhancement of adolescents’ psychological well-being. In the last section which centers on Educational Psychology, various factors which have impacts upon students, which may include emotional intellegence, study habit, peer groups, emotional sentiments, and mental hygiene etc. are examined. One of these papers reveals that there is a significant composite influence of study habit and test anxiety on the academic performance of secondary school students in Social Studies. Based on the findings of this study, it is recommended among others; that regular counseling services should be introduced to the students in order to train them on study skills strategies which will enable them study harder in Social Studies. In addition, school authorities should work out guidelines as well as develop programmes that will help students to cope with test anxiety in Social Studies. In all, this edition of KIU Journal of Humanities features many empirical and theoretical based articles. Each of them seeks to profer solutions to one social and management problem or the other. Therefore, there is something to learn by every reader of this issue.